DNA-Binding Activities of KSHV DNA Polymerase Processivity Factor (PF-8) Complexes - Jennifer Kneas Travis; Megan Martin; Lindsey M. Costantini (Viruses, 2025)
Kaposi’s Sarcoma Herpesvirus (KSHV) is the causative agent of several human diseases. There are few effective treatments available to treat infection and KSHV oncogenesis. Disrupting the KSHV infectious cycle would diminish the viral spread. The KSHV lytic phase and production of new virions require efficient copying and packaging of the KSHV genome. KSHV encodes its own lytic DNA replication machinery, including the processivity factor (PF-8), which presents itself as an attractive target for antiviral development. We characterized PF-8 at the single molecule level using transmission electron microscopy to identify key molecular interactions that mediate viral DNA replication initiation. Our results indicate that PF-8 forms oligomeric ring structures (tetramer, hexamer, and/or dodecamer) similar to the related Epstein–Barr virus processivity factor (BMRF1). Our DNA positional mapping revealed high-frequency binding locations of PF-8 within the lytic origin of replication (OriLyt). A multi-variable analysis of PF-8 DNA-binding activity with three mutant OriLyts provides new insights into the mechanisms that PF-8 associates with viral DNA and complexes to form multi-ring-like structures. Collectively, these data enhance the mechanistic understanding of the molecular interactions (protein–protein and protein-DNA) of an essential KSHV DNA replication protein.